Danger signals released during cold ischemia storage activate NLRP3 inflammasome in myeloid cells and influence early allograft function in liver transplantationResearch in context - Fernando Lucas-Ruiz; Sandra V. Mateo; Marta Jover-Aguilar; Felipe Alconchel; Laura Martínez-Alarcón; Carlos de Torre-Minguela; Daniel Vidal-Correoso; Francisco Villalba-López; Víctor López-López; Antonio Ríos-Zambudio; José A. Pons; Pablo Ramírez; et al. (EBioMedicine, 2023)
Summary: Background: Innate immunity plays a fundamental role in solid organ transplantation. Myeloid cells can sense danger signals or DAMPs released after tissue or cell damage, such as during ischemia processes. This study aimed to identify DAMPs released during cold ischemia storage of human liver and analyze their ability to activate the inflammasome in myeloid cells and the possible implications in terms of short-term outcomes of liver transplantation. Methods: 79 samples of organ preservation solution (OPS) from 79 deceased donors were collected after cold static storage. We used different analytical methods to measure DAMPs in these end-ischemic OPS (eiOPS) samples. We also used eiOPS in the human macrophage THP-1 cell line and primary monocyte cultures to study inflammasome activation. Findings: Different DAMPs were identified in eiOPS, several of which induced both priming and activation of the NLRP3 inflammasome in human myeloid cells. Cold ischemia time and donation after circulatory death negatively influenced the DAMP signature. Moreover, the presence of oligomeric inflammasomes and interleukin-18 in eiOPS correlated with early allograft dysfunction in liver transplant patients. Interpretation: DAMPs released during cold ischemia storage prime and activate the NLRP3 inflammasome in liver macrophages after transplantation, inducing a pro-inflammatory environment that will complicate the outcome of the graft. The use of pharmacological blockers targeting DAMPs or the NLRP3 inflammasome in liver ischemia during static cold storage or through extracorporeal organ support could be a suitable strategy to increase the success of liver transplantation. Funding: Fundación Mutua Madrileña and Instituto de Salud Carlos III, Madrid, Spain.